Electronic participation third IFIP WG 8.5 international conference, ePart 2011, Delft, The Netherlands, August 29-September 1, 2011. proceedings - ePart (Conference) 2011 Delft, Netherlands); Tambouris, Efthimios; Macintosh, Ann.; Bruijn, Hans.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the Third International Conference on Electronic Participation, ePart 2011, held in Delft, The Netherlands, in August/September 2011. The 26 revised full papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on appreciation of social media; visualizing arguments; understanding eParticipation; eParticipation initiatiaves and country studies; participation and eServices; and innovative technologies.
Electronic reproduction.
Keywords: Political participation -- Computer networks -- Congresses; Political participation -- Technological innovations -- Congresses; Internet in public administration -- Congresses; Electronic voting -- Congresses; Internet voting -- Congresses; Electronic books